Clonal Propagation of Walnuts (Juglans spp.): A Review on Evolution from Traditional Techniques to Application of Biotechnology - Kourosh Vahdati; Rasoul Sadeghi-Majd; Adriana F. Sestras; Ricardo Julián Licea-Moreno; Augusto Peixe; Radu E. Sestras (Plants, 2022)
Walnuts (Juglans sp.) are allogamous species. Seed-derived plants are not always superior to the selected parent. Clonal propagation of selected stock plants is an essential requirement for the clonal fidelity of the descendants and to maintain their genetic structure. Selection of the desired plant is realized only after reaching maturity, and characterizing and evaluating the performance of adult trees require a long time. Clonal propagation methods ensure proper transmission of characters to descendants and can be used effectively in breeding programs. The commercialization of a cultivar or rootstock depends on the success of vegetative propagation. Walnuts, like other tree species, are recalcitrant to conventional vegetative propagation methods and even non-conventional in vitro culture (micropropagation). Elucidation of factors determining the success of cloning of desired plants would contribute to understanding current limitations for most genotypes of Juglans. We outline the role of grafting and cuttings and stool layering, as well as in vitro culture on walnut multiplication. These techniques are, in practice, entirely different; nevertheless, they are affected by common factors. The incompatibility of stock-scion and the reduced ability of stem cuttings to root are the main bottlenecks for grafting and cutting, respectively. Genotype, age, and physiological status, reinvigoration or rejuvenation-treatment of donor plant, period of harvesting and processing of explants critically affect the results of methods followed. The in vitro culture technology is the most suitable for walnut cloning. This also has constraints that affect commercial propagation of most desired genotypes. We describe comprehensive results and synthesis in this review on the asexual reproduction of walnuts, providing a better comprehension of the limiting factors and the ways to overcome them, with direct implications on commercial propagation and the releasing of outstanding genotypes.